2008
DOI: 10.1149/1.2965456
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Layer Deposition of NiO Films on Si(100) Using Cyclopentadienyl-Type Compounds and Ozone as Precursors

Abstract: NiO films were grown on Si͑100͒ by atomic layer deposition using Ni͑Cp͒ 2 ͑Cp = cyclopentadienyl, C 5 H 5 ͒ or Ni͑EtCp͒ 2 ͓EtCp = ethylcyclopentadienyl, ͑C 2 H 5 ͒͑C 5 H 4 ͔͒ and ozone in the 150-300°C temperature range. The growth temperature dependence of structure, electronic density, and impurity levels for the prepared NiO films was studied using X-ray reflectivity, X-ray diffraction ͑XRD͒, Fourier transform infrared ͑FTIR͒ spectroscopy, time of flight-secondary ion mass spectroscopy ͑ToF-SIMS͒, and trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
50
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 45 publications
5
50
0
Order By: Relevance
“…Because of discrepancies in previous reports of this NiO ALD process, we performed a systematic characterization of the ALD deposition. [ 37,41,42 ] NiO was deposited at a stage temperature of 275 °C and a Ni(Cp) 2 bubbler temperature of 85-90 °C. Under these conditions, measurements of fi lm thickness after 75 cycles for different pulse lengths showed that saturation was achieved after ≈8 s for the Ni(Cp) 2 pulse and ≈3 s for the O 3 pulse as seen in Figure 1 a,b.…”
Section: Resultsmentioning
confidence: 99%
“…Because of discrepancies in previous reports of this NiO ALD process, we performed a systematic characterization of the ALD deposition. [ 37,41,42 ] NiO was deposited at a stage temperature of 275 °C and a Ni(Cp) 2 bubbler temperature of 85-90 °C. Under these conditions, measurements of fi lm thickness after 75 cycles for different pulse lengths showed that saturation was achieved after ≈8 s for the Ni(Cp) 2 pulse and ≈3 s for the O 3 pulse as seen in Figure 1 a,b.…”
Section: Resultsmentioning
confidence: 99%
“…This value corresponds to a growth rate of 0.92 Å per cycle and is within the (wide) range reported earlier for ALD-grown nickel oxide. [7] The XRR data attest the smoothness of the film, with an estimated root-50 mean-square roughness below 1 nm. A microscopic investigation indicates that despite the overall smoothness of the film, many pinholes are present (Figure 2b).…”
mentioning
confidence: 81%
“…After cooling, the product contains 73% Ni by mass according to elemental analysis, which 115 corresponds to Ni 0.74 O. Thus, the ALD reaction between nickelocene and ozone at 230 °C yields, in contrast to what has been assumed in the literature to date, [7,8] a nickel-deficient oxide Ni 0.88 O that exhibits the crystal structure of NiO. Its stoichiometry can be 120 adjusted by annealing ( Figure 5).…”
mentioning
confidence: 94%
See 2 more Smart Citations